Students Error Analysis in Using Preposition “to” and “for” in Simple Past Tense - Alhamid, Ipa Zuhra (INTERACTION: Jurnal Pendidikan Bahasa, 2018)
This study was designed to investigate the students error in using preposition “to” and “for”. English is one of international language, this is important for us to master it. In this era, many science and technology book are written in English. Based on the fact that, learning a foreign language often the learner get difficulties, especially in grammar. They were that error analysis at using preposition “to” and “for” are found in the second grade of MTS Al-Ma’arif 1 aimas. The students error were classified into several kind, error in using preposition “to” and “for”, error in using past tense and error in omission, addition and miss-formation. From the analysis, it was found that, the first errors in miss-formation, with the frequency 56% as the highest number of occurrences. The second level in addition, with frequency 22%l. The finally lower in omission with frequency 21%. In learning English process students make error in using preposition in miss-formation, it happened to do not mastery about the material and also writer found caused the error of students include first language, translation error. Based on the discussion, it is included that the students at the second grade of MTS Al-Ma’arif 1 Aimas still low in understanding function of preposition. The finally the writer hopes that it will help the teacher in their teaching to improving the students ability in learning English.